1997
DOI: 10.1051/rnd:19970305
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relationship between endophyll, primordial germ cells, sickle endoblast and upper layer in cultured avian blastoderms

Abstract: Summary ― By isotopic quail-chicken chimera experiments of the Rauber's sickle or by radioactive labelling and isotopically replacing of the caudal endophyllic sheet in unincubated avian blastoderms, followed by culture, we demonstrated that the displacement of the endophyll by the cranially extending sickle endoblast is not exclusively a mechanical phenomenon, as suggested by earlier studies (Vakaet, 1962 a, b). Indeed, our study suggests that the sickle endoblast also migrates centripetally very soon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Instead of Petri dishes, the culture vessels described by Gaillard [17] figure 7D). In the sections, the much thickened quail upper layer (with a preneural plate-like aspect) was seen to be partially recurved at its rims and enclosed the endophyll ( figure 7E, F) [10][11][12]. This seems to be in agreement with studies from Settle [22] and Zagris [24] figure 211A and IIB).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Instead of Petri dishes, the culture vessels described by Gaillard [17] figure 7D). In the sections, the much thickened quail upper layer (with a preneural plate-like aspect) was seen to be partially recurved at its rims and enclosed the endophyll ( figure 7E, F) [10][11][12]. This seems to be in agreement with studies from Settle [22] and Zagris [24] figure 211A and IIB).…”
Section: Introductionsupporting
confidence: 88%
“…Recent studies [5,6,8,12,13] have yielded new data concerning the structures and developmental events in avian intrauterine germs after bilateral symmetrisation and in unincubated eggs. The terminology [ 13] for the different components of an unincubated quail blastoderm and surrounding structures is represented in figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The different components of an unincubated avian blastoderm are shown in Figure 1. We have shown by the use of the quail-chicken chimera technique that during early incubation Rauber's sickle differentiates into: 1) junctional endoblast by local proliferation of its cells into the neighboring subgerminal ooplasm, and 2) sickle endoblast by centripetal and cranial growth, forming a one-cellthick layer (Callebaut and Van Nueten, 1994;Callebaut et al, 1997b). Our previous studies indicated that the main function (i.e., mesoblast and definitive endoderm induction in the upper layer) of Rauber's sickle in avian blastoderms is homologous with the function of Nieuwkoop's center (Nieuwkoop, 1969(Nieuwkoop, , 1973 in amphibian blastulas.…”
mentioning
confidence: 99%
“…In both types of the present experiments there seems thus to exist a common link between the observed induction phenomena: the presence of ␦ ooplasm in the involved deep structures. Indeed, the nucleus of Pander contains ␦ ooplasm as well as the structures derived from it: i.e., endophyll with associated primordial germ cells (Callebaut, 1987;Callebaut et al, 1997) and (in the present study) sickle endoblast derived cells after colonization of the neighboring ooplasm. In the experiments in which sickle endoblast was interposed between a central subgerminal ooplasmic mass and the isolated antisickle region, two kinds of reactions were observed.…”
Section: Discussionmentioning
confidence: 53%